213k views
5 votes
If f(x) = 3x - 2 and g(x) = 2x + 1, find (f+ g)(x).

O A. X-3
B. X-1
O C. 5x-1
D. 5x-3
SUBM
Helpp me

User Rkj
by
5.2k points

2 Answers

3 votes

Answer:

C. 5x-1

Explanation:

We are asked to find:

(f+g)(x)

This basically is asking us to add f(x) and g(x)

(f+g)(x)=f(x)+g(x)

We know that f(x)=3x-2 and g(x)=2x+1

f(x)+g(x)

(3x-2)+(2x+1)

Combine like terms. Add all the terms with variables, then add all the terms without variables.

(3x+2x) + (-2+1)

5x+(-2+1)

5x+-1

5x-1

(f+g)(x)=5x-1

Therefore, C. 5x-1 is the correct answer choice.

User Steven Craft
by
5.2k points
3 votes
I believe it’s asking you to combine the functions so when you combine like terms you have 2x+3x= 5x and you have -2+1= -1 so the answer is c. 5x-1
User UnionP
by
5.2k points